Electricity Demand and CO Emissions during the COVID-19 Pandemic: The Case of India - Tamilselvan, M.; Srinivasan Palamalai; Kumar, Magesh; Maity, Bipasha; Agrawal, Nidhi (International Journal of Energy Economics and Policy, 2022)
The present study examines the impact of electricity demand on CO emissions in the Indian economy using daily real-time data during the Covid-19 period. The subject was hardly addressed explicitly and quantitatively in environmental studies. Our study applied recently developed non-linear (asymmetric) ARDL and the Quantile ARDL techniques for analysis. The empirical findings confirm the existence of an asymmetric long-run relationship between electricity demand and CO emissions during the Covid-19 pandemic. Furthermore, the results reveal that the decrease (increase) in electric demand leads to a reduction (increase) in CO emissions in the long run. Besides, the results show that the increase in electricity demand generates more CO emissions in the short run. Our study will be helpful for policy-makers and regulators associated with energy and climate change amid the ongoing pandemic crisis and provide directions to the expected waves of pandemic scenarios.